Prevalence of refractive errors among pre-school children at King Abdulaziz Medical City, Riyadh, Saudi Arabia - Al-Rowaily, Mohammad A. (Elsevier, 2010)
BACKGROUND: Vision disorders are the fourth most common disability of children and the leading cause of handicapping conditions in childhood. The present study was undertaken to identify the prevalence and pattern of refractive errors among the school-entrant children at King Abdul Aziz Medical City (KAMC), Riyadh city – Kingdom of Saudi Arabia. METHODS: The study population consisted of all the school-entrants (n = 1319), who attended the obligatory health examination for kindergarten and primary school entry during the period from March 2008 until October 2008. Every child was subjected to a 10 min – visual acuity test (VAT) and autorefractive test applied by qualified optometrist. Children with a visual acuity of 20/28 or worse in one or both eyes, or with eye disorder (strabismus, nystagmus, ptosis and others) or abnormal ocular movement, were referred for a 45 min complete ophthalmic examination, which consists of: (1) Distance visual acuity (V/A), (2) cover – uncover test, and (3) non-cycloplpegic retinoscopy. Refractive error cut-off point was defined according to their spherical equivalent refractive error (SERE). RESULTS: Out of the 1319 children, 60 children were diagnosed as having one or more refractive error, with an over-all prevalence of 4.5% (4.2% in boys and 4.9% in girls) with no sex difference. Prevalence of different refractive errors were as follows; Myopia (2.5%, 95%CI1.7:3.3%), hyperopia (2.1%, 95%CI 1.3:2.9%), astigmatism (2.5%, 95%CI 1.7:3.3%), amblyopia (0.5%, 95%CI 0.1:0.9%) and strabismus (0.5%, 95% CI 0.1:0.9%). CONCLUSION: Our results raise the need for school-based program that provides prescription glasses when needed to students at no cost, through government and non-governmental collaborative fund. However, there is a need for further studies to evaluate the cultural beliefs towards the use of spectacles in Saudi communities.